1986
DOI: 10.1017/s0022112086002306
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of a turbulent shear flow with separation, reverse flow, and reattachment

Abstract: Experiments were performed in the highly turbulent and disturbed flow over a bluff plate with a long splitter plate in its plane of symmetry. The flow separates at the sharp bevelled edge of the bluff plate, forms a free shear layer on top of the reverse-flow region which is bounded on its other side by the splitter plate, and reattaches on the splitter plate over a narrow region curved in spanwise direction. Downstream of reattachment the shear flow adjusts slowly to the wall boundary conditions.Measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(86 citation statements)
references
References 15 publications
14
69
2
Order By: Relevance
“…Comparison of the results to those previously published in the literature, indicates that the same trend has been observed for velocity profiles downstream of a bluff plate (fence) with a splitter plate [101], rows of square plates [102], backward facing step [62], and two-dimensional obstacles [100] and [103]. It was concluded that the only solution to achieve a well-developed velocity profile of the desired thickness was a longer upstream length, which was not possible due to the limited length of the test section of the tunnel.…”
Section: Support Legssupporting
confidence: 83%
“…Comparison of the results to those previously published in the literature, indicates that the same trend has been observed for velocity profiles downstream of a bluff plate (fence) with a splitter plate [101], rows of square plates [102], backward facing step [62], and two-dimensional obstacles [100] and [103]. It was concluded that the only solution to achieve a well-developed velocity profile of the desired thickness was a longer upstream length, which was not possible due to the limited length of the test section of the tunnel.…”
Section: Support Legssupporting
confidence: 83%
“…Akon and Kopp (2016) presented a systematic investigation of surface pressures occurring on surface mounted, three-dimensional bluff bodies, finding that the reduced mean pressure coefficient C * p defined in Ruderich and Fernholz (1986): produces a suitable match for a broad range geometric scales, building aspect ratios, and terrain conditions. Here C p refers to the mean pressure coefficient at the location of interest and C p,min refers to the lowest mean pressure coefficient observed in the tap line under the separation bubble.…”
Section: Reduced Mean Pressure Coefficientsmentioning
confidence: 99%
“…Experimental and computational literature is readily available for two dimensional versions of this flow. 3,4,5,6,7,8,9 Figure 1.1 illustrates the general characteristics of this two dimensional flow. The dominant flow feature is the large recirculation region beneath the unsteady, separated shear layer.…”
Section: Flow Physics Backgroundmentioning
confidence: 99%